2018
DOI: 10.1038/s41467-018-07301-y
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Iron restriction inside macrophages regulates pulmonary host defense against Rhizopus species

Abstract: The original version of this Article contained an error in the spelling of the author Emilien Etienne, which was incorrectly given as Emilien Ettiene. These errors have now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(ii) Aspergillus phagosome biogenesis and mechanisms of killing by AMs. AMs efficiently eliminate phagocytosed Aspergillus conidia within 24 h in acidified phagolysosomes (203,220,238,239). Initial studies on Aspergillus phagosome biogenesis demonstrated rapid acquisition of markers of the early (EEA-1, Rab5, and transferrin receptor) and late endosomal/lysosomal (Rab7, LAMP-1, CD63, and cathepsin D) pathways within 30 to 60 min of phagocytosis, which was regarded as a normal phagosome maturation process (203,238).…”
Section: Physiological Immune Response To a Fumigatus Innate Immunitymentioning
confidence: 99%
See 4 more Smart Citations
“…(ii) Aspergillus phagosome biogenesis and mechanisms of killing by AMs. AMs efficiently eliminate phagocytosed Aspergillus conidia within 24 h in acidified phagolysosomes (203,220,238,239). Initial studies on Aspergillus phagosome biogenesis demonstrated rapid acquisition of markers of the early (EEA-1, Rab5, and transferrin receptor) and late endosomal/lysosomal (Rab7, LAMP-1, CD63, and cathepsin D) pathways within 30 to 60 min of phagocytosis, which was regarded as a normal phagosome maturation process (203,238).…”
Section: Physiological Immune Response To a Fumigatus Innate Immunitymentioning
confidence: 99%
“…Physiologically, melanin-induced LAP blockade regulated fungal pathogenicity, since the melanin-deficient mutant restored its virulence upon conditional inactivation of Atg5 in myeloid cells in vivo (200). Of interest, melanin-induced LAP blockade depends on its Ca 2ϩ binding properties and the ability of melanized conidia to inhibit a specialized Ca 2ϩ calmodulin signaling pathway regulating LAP (239). Apart from LAP, identifying other phagosome biogenesis pathways regulating Aspergillus immunity should be exploited.…”
Section: Physiological Immune Response To a Fumigatus Innate Immunitymentioning
confidence: 99%
See 3 more Smart Citations